Effectiveness, tolerability and practical application of the newer generation anti-obesity medications - Jeffrey S MacDaniels; Thomas L Schwartz (BioExcel Publishing Ltd, 2016)
Objective: Comparison of the efficacy and tolerability of five newer anti-obesity medications to guide clinical decision making, examining bupropion-naltrexone combination, liraglutide, lorcaserin, orlistat, and phentermine-topiramate combination. Methods: A brief literature review and internet search for high-powered, randomized and placebo-controlled drug trials was conducted. Drug trial information was established for five currently approved anti-obesity medications. Secondarily, a statistical comparison of medications through Number Needed to Treat (NNT) and Number Needed to Harm (NNH) analyses were attempted as a way to provide a clinical analysis across these varied medications. Finally, a commentary about clinical application is issued for each agent accounting for typical side-effects, serious side-effects, mechanism of action and ease of use. Results: All five agents are currently approved oral medications to lower weight. The NNT range was 3-12, and NNH range was 4-17. The agent with the best NNT is phentermine-topiramate combination (NNT=3) and the agent with the best NNH is bupropion-naltrexone combination (NNH=17). Conclusion: When considering each patient's clinical presentation, knowledge of each drug's mechanism of action, side-effect profile, efficacy, and NNT and NNH values can help in selecting an anti-obesity medication to augment his or her weight loss efforts.